A survey of minimally invasive cardiac surgery during the COVID-19 pandemic. (November 2022) - Lyons, Megan; Akowuah, Enoch; Hunter, Steve; Caputo, Massimo; Angelini, Gianni D; Vohra, Hunaid A
Background: Lack of scientific data on the feasibility and safety of minimally invasive cardiac surgery (MICS) during the COVID-19 pandemic has made clinical decision making challenging. This survey aimed to appraise MICS activity in UK cardiac units and establish a consensus amongst front-line MICS surgeons regarding standard best MICS practise during the pandemic. Methods: An online questionnaire was designed through the 'googleforms' platform. Responses were received from 24 out of 28 surgeons approached (85.7%), across 17 cardiac units. Results: There was a strong consensus against a higher risk of conversion from minimally invasive to full sternotomy (92%; n  = 22) nor there is increased infection (79%; n  = 19) or bleeding (96%; n  = 23) with MICS compared to full sternotomy during the pandemic. The majority of respondents (67%; n  = 16) felt that it was safe to perform MICS during COVID-19, and that it should not be halted (71%; n  = 17). London cardiac units experienced a decrease in MICS (60%; n  = 6), whereas non-London units saw no reduction. All London MICS surgeons wore an FP3 mask compared to 62% ( n  = 8) of non-London MICS surgeons, 23% ( n  = 3) of which only wore a surgical mask. London MICS surgeons felt that routine double gloving should be done (60%; n  = 6) whereas non-London MICS surgeons held a strong consensus that it should not (92%; n  = 12). Conclusion: Whilst more robust evidence on the effect of COVID-19 on MICS is awaited, this survey provides interesting insights for clinical decision-making regarding MICS and aids to facilitate the development of standardised MICS guidelines for an effective response during future pandemics.